The delicate balance between bleeding and thrombosis in cardiac patients undergoing thoracic surgery - Omer Baygin; Didem Gungor Arslan; Ayten Saracoglu (Global Journal of Anesthesiology - Peertechz Publications, 2018)
Management of perioperative anti-coagulation is a general clinical dilemma, and generally accompanied by the signifi cant adverse effects. A personalized approach is necessary to minimize the risks of anesthesia and surgery in patients with comorbidities. Patients with coronary artery disease may not tolerate decreased oxygen delivery and increased oxygen demand in myocardium due to bleeding.On the other side there is an increased use of new anticoagulants in thoracic surgery. The essentials of perioperative management should be determined by creating a balance between the use of oral anticoagulants in low bleeding risk, and bridging treatment for patients having high thromboembolic risk. In this opinion article, we aimed to review the factors affecting bleeding and thrombosis during thoracic surgery. Classifi cation of bleeding and thrombosis risk in cardiac patients was reviewed with the recommendations for preventing the thrombotic complications.